If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 2 = 42 Reorder the terms: 2 + 3x = 42 Solving 2 + 3x = 42 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 3x = 42 + -2 Combine like terms: 2 + -2 = 0 0 + 3x = 42 + -2 3x = 42 + -2 Combine like terms: 42 + -2 = 40 3x = 40 Divide each side by '3'. x = 13.33333333 Simplifying x = 13.33333333
| x(x+2)=159+6(x+x+2) | | 8=3x^2-2x | | 8=3x*3x-2 | | X=3+0.25x | | X=3+0.25 | | 3Q=2P-M | | 2x-4u-5=0 | | (343)1/4(343)-1/12 | | 3(2p-7)=4p-5 | | f(-3)=-3 | | 8X+14=38+2x | | 8X+14=38+2 | | h^2-2h=0 | | 2x+3=10-3x | | 1/2X7 | | 10x-4=5x+15 | | 12-(-y-19)=12 | | 5z^2-4z^4-4=0 | | x=(5x-6)+21 | | 23X-5X^2=-24 | | 4.6=5.8-p | | -(-3-7g)-11=-9-5g | | 6x^2-73x-63=0 | | 3[x-3]+2=13-x | | 3a+7(5a+7b)-10(3+5b)=14ab+50(3+4) | | 2[3x+2(x-2)]+19=(3x+1)*2 | | 8x+3-(7+9x)=-8 | | 2(3c+2d)-2(5c-3d)= | | -(3y-1)-3y+7=2 | | 2x^3-11x^2-x+5=0 | | 3(x+2)=5(3x-2) | | y=x^4-2x^3-3x^2 |